Utazás az első világháború alatt - Suba, János (Közép-Európai Közlemények, 2015)
Before the war, passport and visa became common for those who traveled abroad. During the war, traveling into and across the country was limited for foreigners. Restrictions came into force within the territory of the country and the operational areas. It meant the introduction of various traveling documents, which were different for civil individuals and soldiers. This way they could filter the travellers as well as control them. Special traveling documents were used: there were ones to get into the operational areas, to move within, to leave them and to enter and stay in the occupied territories. An other paper was required to travel into the allied states. The validity of these documents applied to the defined theatre of war and the operational area within it, as well as a certain period of time.